How can eDNA contribute in riverine macroinvertebrate assessment? A metabarcoding approach in the Nalón River (Asturias, Northern Spain). Issue 4 (20th October 2019) - Fernández, Sara; Rodríguez‐Martínez, Saúl; Martínez, Jose L.; Garcia‐Vazquez, Eva; Ardura, Alba
Abstract: Background: Bioassessment of rivers is a fundamental method to determine surface water quality. One of the groups most commonly employed as bioindicators of aquatic ecosystems are benthic macroinvertebrates. Their conventional assessment is based on morphological identification and entails several limitations, such as being time‐consuming and requires trained experts for taxonomic identification. The use of genetic tools to solve these limitations offers an alternative way to evaluate rivers status. The use of environmental DNA (eDNA) metabarcoding has increased in recent years for different purposes, but its use in water quality evaluation is yet to be tested. Here, morphological and eDNA based inventories of macroinvertebrates were compared from the same seven sampling sites in the Upper Nalón River Basin (Asturias, Spain). Materials & Methods: High‐Throughput Sequencing (HTS) of the cytochrome oxidase subunit 1 (COI) gene was carried out on DNA from water samples using an Ion Torrent platform. Biotic water quality indices were calculated from morphological and molecular data and compared with independent physico‐chemical habitat assessment to validate eDNA based approach. Results: Highly positive and significant correlation was found between eDNA metabarcoding and morphological methods (Morphological and eDNA indices, r = 0.798, 5 degrees of freedom d.f., P = 0.031;) and a highly significant negative correlation was found between molecular and habitat quality indices (Stress score & eDNA, ρ = ‐0.878 and P = 0.009; Stress score & Visual, ρ = ‐0.949 and P = 0.0002). Discussion: The similarity of results from the two approaches and the correlation of eDNA metabarcoding data with the habitat quality indices, suggest that eDNA performs as well as conventional methods for calculating biotic indices in this system, positioning eDNA metabarcoding of macroinvertebrate communities to transform how river bioassessment can be achieved. Conclusion: The usefulness of eDNA metabarcoding to assess rivers water quality based on macroinvertebrates assessment has been demonstrated in a dammed river basin. Abstract : Rivers are impacted ecosystems that need to be monitored regularly. Here, we have tested a metabarcoding approach to compare the results on water quality monitoring with conventional assessments for benthic macroinvertebrates. Water quality monitoring in freshwaters using macroinvertebrate eDNA performs equally well than conventional morphological‐based monitoring.